2023
DOI: 10.9734/acri/2023/v23i5573
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and Epidemiological Characterisation of Leprosy in the Population of Pará, Amazon, from 2016 to 2020

Abstract: Objective: To describe the sociodemographic and epidemiological characteristics of the population with leprosy in the State of Pará from 2016 to 2020. Methodology: Cross-sectional ecological study, based on data from the Disease Information and Notification System (SINAN). The study was conductedin 144 municipalities in Pará, Amazon. The data were organised and distributed by 12 integration Regions. Results and Discussion: In the analysed data, a total of 11,687 cases of leprosy were verified in Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Findings related to demographic factors in this study, which seemed to affect the domains of ICF disability, have been observed in other studies. Most of the patients in this study were males within the range of productive age group, as also found in other studies from Indonesia, Brazil, and India [43][44][45][46]. Our results also showed that body function, activity limitation, and participation restriction had positive correlations with age.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Findings related to demographic factors in this study, which seemed to affect the domains of ICF disability, have been observed in other studies. Most of the patients in this study were males within the range of productive age group, as also found in other studies from Indonesia, Brazil, and India [43][44][45][46]. Our results also showed that body function, activity limitation, and participation restriction had positive correlations with age.…”
Section: Discussionsupporting
confidence: 90%
“…More than half of this study population also had low educational attainment, indicating a shared context of socioeconomic vulnerability. This trend has been observed in Indonesian, Indian, and Brazilian studies by Menaldi et al [8], Karotia et al [49], and Dergan et al [46], respectively. Individuals possessing higher levels of education are believed to adopt health-conscious lifestyles, actively acquire medical knowledge, and mitigate the risk of disability [50].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Most of the patients in this study were males within the range of productive age group, as also found in other studies from Indonesia, Brazil, and India. [37][38][39][40] Our results also showed that body function, activity limitation, and participation restriction had positive correlations with age. Higher male population in leprosy cases could be attributed to differences in sociocultural behaviours between genders and life choices that would lead to higher risk of contracting the infection.…”
Section: Resultssupporting
confidence: 68%
“…This trend has been observed in Indonesian, Indian Unfortunately, diagnostic timepoints and treatment dropout were not explored. [8,40,42] Leprosy patients with multi-bacillary type demonstrate more pronounced physical dysfunction and experience greater bodily pain when compared to the pauci-bacillary group, which primarily stems from nerve impairment in leprosy patients. [43] Multi-bacillary patients were significantly at higher risk of developing nerve-function impairment.…”
Section: Resultsmentioning
confidence: 99%